Multibeam bathymetry processed data (Kongsberg EM 122 working area dataset) of RV MARIA S. MERIAN during cruise MSM69, St Paul Fracture Zone, Atlantic Ocean - Gregory, Emma P M; Villinger, Heinrich; Singh, Satish C; Kaul, Norbert; Grevemeyer, Ingo (PANGAEA, 2023)
A geophysical study was undertaken over the St Paul Fracture Zone in the Equatorial Atlantic Ocean in November and December of 2017, during research cruise MSM69 aboard the German vessel RV Maria S. Merian (Grevemeyer et al., 2019). Data acquired included a grid of multibeam bathymetry data of the seafloor topography along and across the fracture zone. Processing steps for the multibeam data included: manual cleaning to remove erroneous points; conversion to depth using sound velocity profiles derived from CTD data acquired during the cruise; and navigation correction for the position of the echosounder on the ship. Tide correction was not applied due to the large water depth. Here, we present gridded multibeam bathymetry data of the eastern St Paul Fracture Zone, located between 1°N – 2.5°N and 19°W – 17°W. This is provided in both GMT NetCDF grid and GeoTIFF formats, with a grid resolution of 100 m (approximately 0.0009°).
Keywords: Bathymetry; Equatorial Atlantic; fracture zones; sub-bottom profiles